(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: This study aims to describe the inpatient treatment costs and associated factors of inpatient cost of patients with Tuberculosis at the Bac Giang Lung Hospital in 2024. Subjects and Methods: A cross-sectional descriptive study using retrospective data from medical records and hospital invoices of inpatient in 2024. The total number of inpatients in this study was 405 patients. Descriptive analysis of mean, min, max and percentage was used to calculate the direct medical cost of TB patients. Linear regression was used to find associated factors of inpatients treatment costs Results: The average total treatment cost per patient was VND 8.514.000. The associated factors included length stay, type of Tuberculosis and number of comorbidities. The average cost of inpatient care increases with longer hospital stays, a higher number of comorbid conditions, and multidrug-resistant cases. Conclusion: The treatment cost of tuberculosis is considerably high, associated factors included length of stay, number of comorbid conditions, and type of Tuberculosis